Co2sno4/Carbon Nanotubes Composites: A Novel Approach for Electrochemical Sensing of Hydrogen Peroxide - Ruiz-Leon, D; Ruiz-Leon, D; Brito-Ramírez, T (Wiley-VCH Verlag, 2018)
For the first time Co2SnO4 (CTO)/Carbon nanotubes (CNT) composites were prepared and used to modify glassy carbon electrodes for the amperometric determination of hydrogen peroxide. The catalytic activity of composites towards the oxidation of hydrogen peroxide was dependent on the quantity of CNT present in the composite and to the pH of the medium. The pure cobalt stannate phase with a ratio of 3 : 1 (CTO:CNT) exhibited the best catalytic activity towards hydrogen peroxide oxidation at low potentials (0.200 and 0.500 V). A linear relationship between current and hydrogen peroxide concentration was obtained with a sensitivity of 95 and 258 μA mM−1 and a detection limit of 0.130 and 0.08 μM respectively. © 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim